Atração de peixes silvestres em área aquícola subtropical do estado do Paraná, Brasil - Benfatti, Ladislao Wychoski (2020)
The present study evaluated the ichthyofauna near the cage aquaculture installed in the Salto Caxias reservoir, through spatial and temporal patterns in the composition, abundance (numerical and weight), structure and distribution of the resident ichthyofauna. Collections were carried out quarterly between July 2010 and November 2012, in two semi-identical stretches established on the Jacutinga River (control) and in the section close to the Iguaçu River Technological Diffusion and Development Center (CDT) (aquaculture section). The fish were captured, anesthetized, identified, counted and weighed. A total of 2662 individuals sere sampled were captured, 58.11% of that captured was aquaculture area, and for both stretches, phase 2 showed greater capturability. In total 38 species belonging to six orders distributed in 15 families were registered. Most species are small and common in both stretches. The attributes of communities were high in the aquaculture section and in phase 2, except for evenness, which was lower in the second phase. The ordering (Principal Coordinates Analyses - PCoA) showed distinction in the distribution of abundance and weight (CPUE no. Ind. And kg / 1000m2 net / 24h) of the species between the stretches and phases, being phase 2 of the aquaculture area was distinct. The dissimilarity between the assemblies was 47.62% and ten species contributed to this dissimilarity (80.49% cumulative). It is concluded that the aquatic biota is affected by the fish farming activity.